Ruzigrass affecting soil-phosphorus availability - Merlin, Alexandre [UNESP]; He, Zhenli Li [UNESP]; Rosolem, Ciro Antonio [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2013)
The objective of this work was to evaluate the effectiveness of ruzigrass (Urochloaruziziensis) in enhancing soil-P availability in areas fertilized with soluble or reactive rock phosphates. The area had been cropped for five years under no-till, in a system involving soybean, triticale/black-oat, and pearl millet. Previously to the five-year cultivation period, corrective phosphorus fertilization was applied once on soil surface, at 0.0 and 80 kg ha-1 P2O5, as triple superphosphate or Arad rock phosphate. After this five-year period, plots received the same corrective P fertilization as before and ruzigrass was introduced to the cropping system in the stead of the other cover crops. Soil samples were taken (0-10 cm) after ruzigrass cultivation and subjected to soil-P fractionation. Soybean was grown thereafter without P application to seed furrow. Phosphorus availability in plots with ruzigrass was compared to the ones with spontaneous vegetation for two years. Ruzigrass cultivation increased inorganic (resin-extracted) and organic (NaHCO3) soil P, as well as P concentration in soybean leaves, regardless of the P source. However, soybean yield did not increase significantly due to ruzigrass introduction to the cropping system. Soil-P availability did not differ between soluble and reactive P sources. Ruzigrass increases soil-P availability, especially where corrective P fertilization is performed.

O objetivo deste trabalho foi avaliar a eficácia da braquiária (Urochloa ruziziensis) em aumentar a disponibilidade de P, em solo de áreas fertilizadas com fosfatos solúveis ou reativos. A área havia sido cultivada em semeadura direta por cinco anos, em sistema de cultivo com soja, triticale/aveia-preta e milheto. Previamente ao período de cinco anos de cultivo, aplicou-se adubação corretiva de P à superfície do solo, com 0,0 ou 80,0 kg ha-1 P2O5, nas formas de superfosfato triplo ou fosfato Arad. Após esse período de cinco anos, as parcelas receberam a mesma adubação corretiva de antes, e a braquiária foi introduzida no sistema de cultivo no lugar das outras plantas de cobertura. Após o cultivo da braquiária, foram coletadas amostras de solo, na camada 0-10 cm, e submetidas ao fracionamento de P. A soja foi cultivada em seguida, sem adubação fosfatada no sulco de plantio. A disponibilidade de P nas parcelas com a braquiária foi comparada àquelas com vegetação espontânea, por dois anos. O cultivo da braquiária aumentou os teores de P inorgânico (extraído com resina) e orgânico (NaHCO3) no solo, bem como o conteúdo de P nas folhas da soja, independentemente da fonte de P utilizada. No entanto, a produtividade da soja não aumentou significativamente pela introdução da braquiária ao sistema de cultivo. A braquiária aumenta a disponibilidade de P no solo, especialmente nas áreas com adubação fosfatada corretiva.
Efeito da braquiária sobre a disponibilidade de fósforo no solo
Keywords: Brachiaria ruziziensis; Urochloa ruziziensis; cultivos de cobertura; rotação de culturas; ciclagem de P; fracionamento de fósforo; Brachiaria ruziziensis; Urochloa ruziziensis; cover crops; crop rotation; P cycling; phosphorus fractionation